1981
DOI: 10.1007/bf00210355
|View full text |Cite
|
Sign up to set email alerts
|

Time-related changes in size of nuclei of pinealocytes in rats

Abstract: In a study of 96 adult male Sprague-Dawley rats, da- and time-related changes of the mean nuclear volume of pinealocytes were determined with the aim of testing the reproducibility of the karyometric findings described by Quay and Renzoni (1966). It is shown (i) that statistically significant differences exist between the central and peripheral mean volumes of pinealocyte nuclei/group of animals and time point (p less than 0.001), (ii) that the day and time related differences are statistically different in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…It was reported that the nuclear volume of peripheral pinealocytes was larger than that of central pinealocytes in the superficial pineal of the rat [Diehl, 1981;Becker and Vollrath, 19831 and, in addition, pinealocyte nuclear volumes in many species including the rat were larger in the superficial pineal than in the deep pineal. However, regional differences in a proximodistal direction have not been described in the superficial pineal itself.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It was reported that the nuclear volume of peripheral pinealocytes was larger than that of central pinealocytes in the superficial pineal of the rat [Diehl, 1981;Becker and Vollrath, 19831 and, in addition, pinealocyte nuclear volumes in many species including the rat were larger in the superficial pineal than in the deep pineal. However, regional differences in a proximodistal direction have not been described in the superficial pineal itself.…”
Section: Discussionmentioning
confidence: 97%
“…In the superficial pineal of the rat, differences in nuclear size of pinealocytes have previously been described between peripheral and central regions [Diehl, 1981;Becker and Vollrath, 19831. In these studies, however, regional differences in a proximodistal direction have not been considered.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the majority of these studies light microscopic karyometry has been used. Usually, karyometric results show higher values during daytime as compared to those at night (rat: Becker and Vollrath, 1983;Diehl, 1981;Quay and Renzoni, 19661, though no differences over a 24-hour period have been shown (gerbil: Welsh et al, 1979a). In recent electron-microscopic studies of the rat pinealocytes we found larger nuclear cross-sectional areas at night as compared to those during daytime (Karasek et al, 1990).…”
Section: Quantitative Ultrastructurementioning
confidence: 94%